Church and state in 21st century Britain: the future of church establishment - Morris, R. M. (Palgrave Macmillan, 2009)
With Church establishment largely locked in the geopolitics of the late 17th century, this study examines the case for change. How should the constitution respond to an ever more pluralized society; what are the implications for the religious character of the monarchy? This book helps readers consider such questions and reach their own judgments